2011
DOI: 10.1111/j.1095-8339.2011.01122.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity patterns in Curcuma reflect differences in genome size

Abstract: The relationships between genome size and the systematic and evolutionary patterns in vascular plants are equivocal, although a close relationship between genome size and evolutionary patterns has been previously reported. However, several studies have also revealed the dynamic nature of genome size evolution and its considerable 'ups' and 'downs'. Thus, in this study, the phylogenetic relationships among three previously revealed genome size groups and among species of the highly polyploid genus Curcuma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Divergent ribosomal DNA sequences arise in hybrids due to differences in the evolutionary trajectories of parental sequences during the process of concerted evolution (Alvarez and Wendel ; Bailey et al ). Thus, the results of the present study and previous studies (Leong‐Skornickova et al ; Zaveska et al , ) clearly indicate that Curcuma species are the products of recent hybridization events wherein the concerted evolution of ITS is at an initial phase and the ancestral haplotype of the plastid persists, affecting the barcode potential of both plastid and ITS loci.…”
Section: Discussionsupporting
confidence: 76%
“…Divergent ribosomal DNA sequences arise in hybrids due to differences in the evolutionary trajectories of parental sequences during the process of concerted evolution (Alvarez and Wendel ; Bailey et al ). Thus, the results of the present study and previous studies (Leong‐Skornickova et al ; Zaveska et al , ) clearly indicate that Curcuma species are the products of recent hybridization events wherein the concerted evolution of ITS is at an initial phase and the ancestral haplotype of the plastid persists, affecting the barcode potential of both plastid and ITS loci.…”
Section: Discussionsupporting
confidence: 76%
“…A sexual mode of reproduction is a known mechanism for maintaining high genetic diversity within species. For the genus Curcuma (Zingiberaceae), Záveská et al () found that Nei's gene diversity in sexually‐reproducing diploid taxa is significantly greater than in vegetatively‐reproducing (triploid and pentaploid) taxa. Based on chloroplast DNA sequence divergence (Techaprasan et al, ), this appears to be the case for Kaempferia as well.…”
Section: Discussionmentioning
confidence: 99%
“…) was carried out for 403 individuals using the AFLP Core Reagent Kit I (Invitrogen) and the AFLP Pre‐Amp Primer Mix I (Invitrogen) following the manufacturer's instructions, with modifications described in Záveská et al . () and as follows: DNA (~40 ng) was digested for 12 h at 37 °C with 0.6 U each of EcoRI and MseI (Invitrogen) and 1 μL 5× reaction buffer (Invitrogen) in a total volume of 5 μL. Adaptors were ligated to the digested fragments by adding 4.8 μL adaptor/ligation solution (Invitrogen) and 0.3 U T4 DNA ligase (Invitrogen), and the reaction (total volume 10 μL) was incubated for 12 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%